(untitled) (The Chittagong University Journal of Science, 2018)
Municipal solid waste (MSW) management has an impact on climate generating greenhouse gases (GHG). To quantify GHG emission from MSW management activities (transportation, composting, recycling and landfill), this study was conducted in the Chittagong City Corporation (CCC). Data were collected about detail MSW management activities of the CCC through conducting a structured questionnaire survey on related personnel with MSW management. To collect data about recycling, another questionnaire survey was conducted on all junkshops near to both dumping sites (Anandabazar and Arefin Nogor) of the CCC. The study found that, composting and recycling of MSW have a positive contribution in reducing GHG emission. Transportation and land-filling of MSW have a contribution in GHG emission. The amount of GHG emission from the existing MSW management system of the CCC is 31,904.68 tons of CO2-eq per month. The life cycle assessment (LCA) study on composting shows that, the reduction of GHG emission is 3.66 tons of CO2-eq per ton of produced compost. The study finding is expected to contribute to the field of climate change mitigation in Bangladesh. The Chittagong Univ. J. Sci. 40(1) : 21-46, 2018